Análise comparativa de elementos estruturais em concreto armado empregando armadura de fibra de vidro em relação à convencional de aço - Albuquerque, Samuel Gomes de (Brasil, 2023)
In the present study, a beam and a column were dimensioned, considering reinforcement with glass fiber reinforced polymer (GFRP) bars and conventional steel bars. The same span and environmental conditions were considered for both the beams, and they had identical cross-sections. Additionally, another steel-reinforced beam was calculated using the same parameters as the previous beams, but with an increased height to fall within domain 3. Based on the obtained results, it was possible to compare the reinforced concrete beam with GFRP bars to the one reinforced with steel, and it was observed that reinforced concrete with GFRP bars proved to be an equivalent option for everyday construction. The area of GFRP bar reinforcement was 64.86% larger than that of steel, considering the same beam sections. Furthermore, the column with GFRP bars required a greater longitudinal reinforcement area compared to the steel-reinforced column under the same conditions and is considered slightly more expensive.